Toxin-Antitoxin Genes of the Gram-Positive Pathogen Streptococcus pneumoniae: So Few and Yet So Many - Wai Ting Chan; Inma Moreno‐Córdoba; Chew Chieng Yeo; Manuel Espinosa (2012)
Pneumococcal infections cause up to 2 million deaths annually and raise a large economic burden and thus constitute an important threat to mankind. Because of the increase in the antibiotic resistance of Streptococcus pneumoniae clinical isolates, there is an urgent need to find new antimicrobial approaches to triumph over pneumococcal infections. Toxin-antitoxin (TA) systems (TAS), which are present in most living bacteria but not in eukaryotes, have been proposed as an effective strategy to combat bacterial infections. Type II TAS comprise a stable toxin and a labile antitoxin that form an innocuous TA complex under normal conditions. Under stress conditions, TA synthesis will be triggered, resulting in the degradation of the labile antitoxin and the release of the toxin protein, which would poison the host cells. The three functional chromosomal TAS from S. pneumoniae that have been studied as well as their molecular characteristics are discussed in detail in this review. Furthermore, a meticulous bioinformatics search has been performed for 48 pneumococcal genomes that are found in public databases, and more putative TAS, homologous to well-characterized ones, have been revealed. Strikingly, several unusual putative TAS, in terms of components and genetic organizations previously not envisaged, have been discovered and are further discussed. Previously, we reported a novel finding in which a unique pneumococcal DNA signature, the BOX element, affected the regulation of the pneumococcal yefM-yoeB TAS. This BOX element has also been found in some of the other pneumococcal TAS. In this review, we also discuss possible relationships between some of the pneumococcal TAS with pathogenicity, competence, biofilm formation, persistence, and an interesting phenomenon called bistability.